Determination of in Vitro Digestibility of Tropical Feeds Using Cattle Faeces as Rumen Fluid Alternative - R Utomo; M Soedjono; B P Widyobroto; . Sudirman (Faculty of Animal Science, Bogor Agricultural University, 2011)
The research was conducted to compare the ability of faeces dissolved in distilled water (P1), saline solution (P2), artificial saliva (P3), and rumen fluid (RF) as sources of inoculant in in vitro organic matter digestibilities (IVOMD) of rice straw, corn stover, napier grass, and pangola grass. The rumen fluid was collected from two rumen fistulated Ongole Crossbred Cows of 306 and 333 kg body weight (BW). The cows were fed 3% of BW consisted of 70% napier grass and 30% concentrate. At the end of 30 days feeding, faecal solution was made out of 350 g fresh faeces dissolved in 1 l of each solvent, homogenized using blender for 30 second, while rumen liquor were collected directly from fistula. After straining with four layers of cheesecloth both faecal solution and rumen liquid were mixed with artificial saliva (1:4 v/v). Fifty ml of each inoculants was pipetted into each incubator tube (100 ml) containing 500 mg sample. The tubes were then incubated at 39 oC for 48 h. Value of IVOMD of napier grass, rice straw, corn stover, and pangola grass did not differ among the faecal solvents, but significantly lower (Pin vitro organic matter to predict digestibility of fibrous feed determination. However, the faecal solvent as inoculant produced lower in vitro digestibility than that of rumen fluid.